Studi tentang Akuntabilitas Pengelolaan Alokasi Dana Desa di Maccini Baji, Kabupaten Jeneponto - Ridwan, Muhammad; Anwar, Samsinar; Idrus, Mukhammad (Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This  study  aims  to  describe  the  accountability  of  village  fund  allocation management. Data collection was carried out using in-depth interview  methods, observation methods and documentation methods in the form of 2018  village financial management  reports and other supporting reports. Data analysis was performed using descriptive analysis. The results of this study indicate that in the village  fund  allocation  planning  process  the  principles  of  participation  and transparency have been implemented, the process of implementing village fund allocations has applied the principles of transparency and accountability, and the reporting and accountability process for village fund allocation has applied the principle of accountability.Penelitian ini bertujuan untuk mendeskripsikan akuntabilitas pengelolaan alokasi dana desa. Pengumpulan data dilakukan dengan menggunakan metode wawancara mendalam, metode observasi dan metode dokumentasi berupa laporan pengelolaan keuangan desa 2018 dan laporan pendukung lainnya. Analisis data dilakukan dengan menggunakan analisis deskriptif. Hasil penelitian ini menunjukkan bahwa dalam proses perencanaan alokasi dana desa prinsip partisipasi dan transparansi telah diterapkan, proses pelaksanaan alokasi dana desa telah menerapkan prinsip transparansi dan akuntabilitas, dan proses pelaporan dan akuntabilitas alokasi dana desa. telah menerapkan prinsip akuntabilitas.